Impact of direct seeded rice technology adoption on farm income in Punjab - J, Balaji S; Kumar, Shiv; Nikam, Vinayak R; T, Kingsly I; Jumrani, Jaya; Joshi, Vister; Kumar, Amit (The Indian Journal of Agricultural Sciences, 2020)
The study isolates the impact of DSR technology on farm household well-beings in the state of Punjab using PSM technique on data pertaining to 2017-18. The results conclude that adopters of DSR technology have reduced their labor cost, and irrigation cost significantly, besides a marginal improvement in yield of paddy. The cost cutting on inputs and a slight improvement in yield due to this technology yielded a higher net income of about Rs. 8100/ ha compared to non adopters.